Cities near volcanoes: which cities are most exposed to volcanic hazards? - E. S. Meredith; E. S. Meredith; R. X. N. Teng; S. F. Jenkins; J. L. Hayes; S. Biass; H. Handley; H. Handley (Natural Hazards and Earth System Sciences)
Cities near volcanoes expose dense concentrations of people, buildings, and infrastructure to volcanic hazards. Identifying cities globally that are exposed to volcanic hazards helps guide local risk assessment for better land-use planning and hazard mitigation. Previous city exposure approaches have used the city centroid to represent an entire city and assess population exposure and proximity to volcanoes. However, cities can cover large areas and populations may not be equally distributed within their bounds, meaning that a centroid may not accurately capture the true exposure. In this study, we suggest a new framework to rank global city exposure to volcanic hazards. We assessed global city exposure to volcanoes in the Global Volcanism Program database that are active in the Holocene by analysing populations located within 10, 30, and 100 km of volcanoes. These distances are commonly used in volcanic hazard exposure assessment. City margins and populations were obtained from the Global Human Settlement (GHS) model datasets. We ranked 1133 cities based on the number of people exposed at different distances from volcanoes, the distance of the city margin from the nearest volcano, and the number of nearby volcanoes. Notably, 50 % of people living within 100 km of a volcano are in cities. We highlight Jakarta, Bandung, and San Salvador as scoring highly across these rankings. Bandung in Indonesia ranks highest overall, with over 8 million people exposed within 30 km of up to 12 volcanoes. South-East Asia has the highest number of exposed city populations (∼ 161 million). Jakarta (∼ 38 million), Tokyo (∼ 30 million), and Manila (∼ 24 million) have the largest number of people within 100 km. Central America has the highest proportion of its city population exposed, with Quezaltepeque and San Salvador exposed to the most volcanoes (n = 23). Additionally, we ranked the 1264 Holocene volcanoes by city populations exposed within 10, 30, and 100 km, the number of nearby cities, and the distance to the nearest city. Tangkuban Parahu, Tampomas, and San Pablo Volcanic Field score highly across these rankings. Notably, the Gede-Pangrango (∼ 48 million), Tangkuban Parahu (∼ 8 million), and Nejapa-Miraflores (∼ 0.8 million) volcanoes have the largest city populations within 100, 30, and 10 km, respectively. We developed a web app to visualize all cities with over 100 000 people exposed. This study provides a global perspective on city exposure to volcanic hazards, identifying critical areas for future research and mitigation efforts.